Stigma toward people living with HIV among healthcare providers in midwifery hospitals in Shenzhen, China from 2020 to 2023 - Leilei Yuan; Xiaoyue Peng; Dadong Wu; Siqi Chen; Wenting Tang; Hong Wang; Jie Zhou (Scientific Reports)
Abstract Shenzhen, a leading city in China’s Elimination of Mother-to-Child Transmission (EMTCT) Programme, implemented effective practices to reduce HIV-related stigma and officially launched a comprehensive work plan in 2021. This study assessed the trend of HIV-related stigma in Shenzhen’s midwifery hospitals by comparing two surveys of healthcare providers (HCPs) conducted in 2020 and 2023. The study included 2705 HCPs and used an adapted 15-item HIV-related stigma scale. The results showed a significant decrease in stigma, with the mean stigma score dropping from 2.01 in 2020 to 1.89 in 2023. While most items showed improvement, one item related to prejudice and stereotypes showed a slight increase in stigma. In two items on attitudes toward women living with HIV, HCPs were more supportive of their reproductive rights, but less so toward allowing women living with HIV with children to have more. Training was found to be a factor associated with reducing stigma. HCPs who did not receive training, were older, worked as nurses, or had no HIV patient service experience exhibited higher levels of stigma. In general, our findings suggest that the EMTCT programme may contribute to reducing HIV-related stigma, highlighting the importance of continued training and programme optimization to address persistent stigma.